Estudo comparativo dos regimes de tributação na importação de bens do exterior - Cardoso, Ricardo (2014)
This research had as its theme the various forms of taxation that may be subject imported goods from abroad. We attempted to make a comparison between the common type of import and import rules Simplified, Special, and Unified, considering their respective advantages and disadvantages for importers.